Impaired mobility drives disability in psoriatic arthritis – An observational study from Karnataka Psoriatic Arthritis Cohort (KPsAC) - Vineeta Shobha; Chanakya Kodishala; S Chandrashekara; Sharath Kumar; Vikram Haridas; Vijay Rao; Ramesh Jois; Manisha Daware; Yogesh Preet Singh; Shweta Singhai; B G Dharmanad; Pramod Chebbi; et al. (Indian Journal of Rheumatology, 2023)
Introduction: Psoriatic arthritis (PsA) is a chronic inflammatory disease with significant functional impairment. Health Assessment Questionnaire-Disability Index (HAQ-DI) is a reliable and validated outcome measure for a variety of arthritides including PsA. Objective: The objective of this study was to assess the disability as an outcome measure in PsA using the Indian version of HAQ (I-HAQ). Methods: The I-HAQ was administered to PsA patients diagnosed as per the Classification Criteria for PsA. The I-HAQ comprises 12 questions (nine basic and three advanced activities of daily living (ADLs), on the standard HAQ format) relevant to the Indian population. Results: In the 549 participants, the mean I-HAQ was 0.31 (0.45) and 48.2% had mild-to-moderate disability (I-HAQ>0–1). Female gender, older age, higher skin, joint scores, and Disease Activity Index for PsA were associated with some disability (I-HAQ>0). Symmetric polyarthritis (0.34) and spondyloarthritis (0.32) had a significantly higher disability compared to other subsets. Analyzing the individual questions of I-HAQ, squatting in the toilet or sitting cross-legged on the floor (r = 0.78), walking 3 km (r = 0.77), and climbing a flight of stairs (r = 0.74) correlated maximally to the total I-HAQ. ADL which was affected most frequently was “climbing a flight of stairs.” I-HAQ was significantly lower in patients who had been on disease-modifying antirheumatic drugs for 6 months or more (P = 0.0001). Conclusions: The Indian version of HAQ-DI could be efficiently employed to assess outcomes in our cohort. Nearly half of the cohort had mild-to-moderate disability suggesting a high burden of inflammation. Higher joint activity scores are strongly associated with disability.